Long-Term Antitumor CD8(+) T Cell Immunity Induced by Endogenously Engineered Extracellular Vesicles - Ferrantelli, Flavia (Cancers (Basel), 2021)
SIMPLE SUMMARY: The induction of an effective immune response against tumor cells is of a great benefit in the battle against cancers. We recently characterized a novel, safe, and cost-effective strategy to induce an efficient CD8(+) T cell immune response against potentially whatever antigen. This technique is based on in vivo engineering of exosomes/extracellular vesicles (EVs), i.e., nanovesicles constitutively released by all healthy cells. Immunogenic EVs are generated by intramuscular injection of a DNA vector expressing an EV-anchoring protein fused with the antigen of interest. In this paper, we applied our vaccine platform to counteract the growth of tumors expressing antigens of Human Papilloma Virus (HPV). We demonstrated that this method is instrumental in curing mice already developing HPV-related tumors. In addition, cured mice were shown to resist a second tumor cell implantation. These results could be of relevance for a possible translation into the clinic of our technology. ABSTRACT: We developed an innovative method to induce antigen-specific CD8(+) T cytotoxic lymphocyte (CTL) immunity based on in vivo engineering of extracellular vesicles (EVs). This approach employs a DNA vector expressing a mutated HIV-1 Nef protein (Nef(mut)) deprived of the anti-cellular effects typical of the wild-type isoform, meanwhile showing an unusual efficiency of incorporation into EVs. This function persists even when foreign antigens are fused to its C-terminus. In this way, Nef(mut) traffics large amounts of antigens fused to it into EVs spontaneously released by the recipient cells. We previously provided evidence that mice injected with a DNA vector expressing the Nef(mut)/HPV16-E7 fusion protein developed an E7-specific CTL immune response as detected 2 weeks after the second immunization. Here, we extended and optimized the anti-HPV16 CD8(+) T cell immune response induced by the endogenously engineered EVs, and evaluated the therapeutic antitumor efficacy over time. We found that the co-injection of DNA vectors expressing Nef(mut) fused with E6 and E7 generated a stronger anti-HPV16 immune response compared to that observed in mice injected with the single vectors. When HPV16-E6 and -E7 co-expressing tumor cells were implanted before immunization, all mice survived at day 44, whereas no mice injected with either void or Nef(mut)-expressing vectors survived until day 32 after tumor implantation. A substantial part of immunized mice (7 out of 12) cleared the tumor. When the cured mice were re-challenged with a second tumor cell implantation, none of them developed tumors. Both E6- and E7-specific CD8(+) T immunities were still detectable at the end of the observation time. We concluded that the immunity elicited by engineered EVs, besides counteracting and curing already developed tumors, was strong enough to guarantee the resistance to additional tumor attacks. These results can be of relevance for the therapy of both metastatic and relapsing tumors.